Molecular and Immunological Characterization of Mycobacterium tuberculosis CFP-10, an Immunodiagnostic Antigen Missing in Mycobacterium bovis BCG - Dillon, Davin C. (American Society for Microbiology, 2000)
In order to identify antigens that may be used in the serodiagnosis of active tuberculosis (TB), we screened a Mycobacterium tuberculosis genomic expression library with a pool of sera from patients diagnosed with active pulmonary TB. The sera used lacked reactivity with a recombinant form of the M. tuberculosis 38-kDa antigen (r38kDa), and the goal was to identify antigens that might complement r38kDa in a serodiagnostic assay. Utilizing this strategy, we identified a gene, previously designated lhp, which encodes a 100-amino-acid protein referred to as culture filtrate protein 10 (CFP-10). The lhp gene is located directly upstream of esat-6, within a region missing in M. bovis BCG. Immunoblot analysis demonstrated that CFP-10 is present in M. tuberculosis CFP, indicating that it is likely a secreted or shed antigen. Purified recombinant CFP-10 (rCFP-10) was shown to be capable of detecting specific antibody in a percentage of TB patients that lack reactivity with r38kDa, most notably in smear-negative cases, where sensitivity was increased from 21% for r38kDa alone to 40% with the inclusion of rCFP-10. In smear-positive patient sera, sensitivity was increased from 49% for r38kDa alone to 58% with the inclusion of rCFP-10. In addition, rCFP-10 was shown to be a potent T-cell antigen, eliciting proliferative responses and gamma interferon production from peripheral blood mononuclear cells in 70% of purified protein derivative-positive individuals without evident disease. The responses to this antigen argue for the inclusion of rCFP-10 in a polyvalent serodiagnostic test for detection of active TB infection. rCFP-10 could also contribute to the development of a recombinant T-cell diagnostic test capable of detecting exposure to M. tuberculosis.